Zürcher Kuh-Kultur. : Land in Sicht - Estermann, Josef; Stadt Zürich (Kreuzlingen : Neptun Verlag AG, 1999)
Aguilar, Vladimir ; Albertin, Vitus ; Alexander, Garda ; Alexander, Günther ; Ambühl, Dani ; Arnold, Rahel ; Arp, Hans (Jean) ; Arpagaus, Gertrud ; Atelier Aroma ; Atelier Pellanda-Berini ; Bächtold, Jörg ; Bächtold, Jürg ; Bandelli, Angela ; Baumann, Christina ; Baumgartner, Rolf ; Beldona-Dekoteam ; Berchtold, Paul ; Berini, A. ; Berini, Arthur ; Bernazzi, Raffael ; Bernegger, Erich ; Bernet, Christoph ; Bill, Max ; Binder, Hannes ; Bisagno, Rico ; Bischofberger, Peter ; Blank, Alain & Verena ; Blau, Magda ; Blum, Heinz ; Bolliger, Vreni ; Bosshard, Sandra ; Brown, Gary ; Brunner, Beat Andreas ; Büchi-Jabiolle, Marie-Christine ; Bühler, Charly ; Bühler, Sylvia ; Burkhard, Brigitt ; Busch, Wilhelm ; Cartier, Paul ; Casanova, Sonia C. ; Caspari, Enrico ; Chopin, Frédérique ; Christo ; Condoleo, Nicola ; Coray, Cia ; Cornelsen, Heiko ; Corpaato, Le Boucher ; Curiger, Irène ; Daim ; Deko Team Seiden Grieder ; Deko-Team Bucherer ; Dekoteam ; Dekoteam Christ ; Devanthey, Cyrano ; Dörig, Ursula ; Drobar, Joe ; Eberhard, Martin ; Ebsqu ; Eggiman, Erwin ; Elsner, Iris ; Ernst Hiestand + Partner AG ; Eyer-Oggier, Denise ; Farbe und Form ; Fasnacht, Benny ; Feldpausch Dekoteam ; Feuerstein-Bucher, Sereina ; Fiorini, Chiara ; Forrer, Brigitte ; Frei, Margot ; Freudiger, Willi ; Furrer, Jürg ; Gentinetta, Anita ; Gerber, Marcel ; Gilg, Hans Peter ; Glazzero, Dario ; Glenser, Tatjana ; Grässle, Marlise ; Gruber, Erich ; Günter, Thomas ; Gurtner-Murphy, Katy ; Gymnasium Rämibühl ; Haring, Keith ; Hartmann, Anna Regula ; Hartmann, Sven ; Hauber, Sylvia ; Heinrich, Dagmar ; Heller, Ruth ; Heusi, Michael ; Hildebrand, Jürg ; Hodler, Ferdinand ; Huber, Cordula ; Huber, Reto ; Hundertwasser ; Hundt, Jutta ; Hürlimann, Rolf ; Isgro, Silvia ; Jansen, Magi ; etc.
Zürcher Kuh-Kultur : Land in Sicht, Eröffnungs am 28. Mai 1998, Sommer 1998
Duits
kunstcatalogus